2018
DOI: 10.1002/jcp.27225
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐186 inhibition of PI3K–AKT pathway via SPP1 inhibits chondrocyte apoptosis in mice with osteoarthritis

Abstract: Chondrocyte apoptosis has been implicated as a major pathological osteoarthritis (OA) change in humans and experimental animals. We evaluate the ability of miR-186 on chondrocyte apoptosis and proliferation in OA and elucidate the underlying mechanism concerning the regulation of miR-186 in OA. Gene expression microarray analysis was performed to screen differentially expressed messenger RNAs (mRNAs) in OA. To validate the effect of miR-186 on chondrocyte apoptosis, we upregulated or downregulated endogenous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…Several miRNAs have been proven to regulate various signaling pathways, apoptosis and chondrocyte functions in OA (28). Some miRNAs are differentially expressed during the onset and development of OA (29)(30)(31). A total of 42 circRNAs have also been found to be differentially expressed in OA (32).…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs have been proven to regulate various signaling pathways, apoptosis and chondrocyte functions in OA (28). Some miRNAs are differentially expressed during the onset and development of OA (29)(30)(31). A total of 42 circRNAs have also been found to be differentially expressed in OA (32).…”
Section: Discussionmentioning
confidence: 99%
“…Through the study of related literature, we found that miR-186 inhibits osteoarthritis chondrocyte apoptosis by interacting with SPP1 and regulating the Phosphatidylinositol‐ 3 kinase (PI3K)/protein kinase B (Akt) pathway. The present study also demonstrates that SPP1 is an important regulator of the PI3K-Akt pathway [32]. As an important signaling pathway related to HNSCC occurrence and development, PI3K-Akt highly affects cell progression, proliferation, migration and survival, and may be activated by G1/S of cell cycle [33], which is also closely related to the occurrence and development of tumors[34].…”
Section: Discussionmentioning
confidence: 73%
“…( 54 ) miR‐186 has been shown to inhibit cathepsin K and the PI3K‐AKT pathway in mice, affecting osteoarthritis and drug‐induced bone deterioration. ( 55,56 ) miR‐19a‐3p and miR‐186‐5p are expressed in bone, brain, and spinal cord tissue as well as in whole blood, ( 57 ) so it is reasonable that these miRNAs may be acting on bone or the SNS (Supplemental Fig. S4 A ).…”
Section: Discussionmentioning
confidence: 99%